The Electronic Structures and Energies of the Lowest Excited States of the Ns0, Ns+, Ns− and Ns-H Defects in Diamond - Platonenko, Alexander; Mackrodt, William C.; Dovesi, Roberto (MDPI, 2023)
This paper reports the energies and charge and spin distributions of the mono-substituted N defects, N0s, N+s, N−s and Ns-H in diamonds from direct Δ-SCF calculations based on Gaussian orbitals within the B3LYP function. These predict that (i) Ns0, Ns+ and Ns− all absorb in the region of the strong optical absorption at 270 nm (4.59 eV) reported by Khan et al., with the individual contributions dependent on the experimental conditions; (ii) Ns-H, or some other impurity, is responsible for the weak optical peak at 360 nm (3.44 eV); and that Ns+ is the source of the 520 nm (2.38 eV) absorption. All excitations below the absorption edge of the diamond host are predicted to be excitonic, with substantial re-distributions of charge and spin. The present calculations support the suggestion by Jones et al. that Ns+ contributes to, and in the absence of Ns0 is responsible for, the 4.59 eV optical absorption in N-doped diamonds. The semi-conductivity of the N-doped diamond is predicted to rise from a spin-flip thermal excitation of a CN hybrid orbital of the donor band resulting from multiple in-elastic phonon scattering. Calculations of the self-trapped exciton in the vicinity of Ns0 indicate that it is essentially a local defect consisting of an N and four nn C atoms, and that beyond these the host lattice is essential a pristine diamond as predicted by Ferrari et al. from the calculated EPR hyperfine constants. © 2023 by the authors.--//-- This is an open access article Platonenko A., Mackrodt W.C., Dovesi R.; The Electronic Structures and Energies of the Lowest Excited States of the Ns0, Ns+, Ns− and Ns-H Defects in Diamond; (2023) Materials, 16 (5), art. no. 1979; DOI: 10.3390/ma16051979; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85149871852&doi=10.3390%2fma16051979&partnerID=40&md5=b11fbcbf91ce1013d1a0e817573fd2fe published under the CC BY 4.0 licence.
This work has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (grant agreement No. 101052200—EUROfusion). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. AP also acknowledges, with thanks, the financial support provided by “Strengthening of the capacity of doctoral studies at the University of Latvia within the framework of the new doctoral model”, No. 8.2.2.0/20/I/006, and Scientific Research Project for Students and Young Researchers, Nr. SJZ/2021/5 implemented at the Institute of Solid State Physics, University of Latvia.
Keywords: Research Subject Categories::NATURAL SCIENCES; B3LYP; C-centre; Gaussian orbitals; N-doped diamond; Ns defects; optical spectra; Δ-SCF calculations